American fire [compact disc, unabridged] : love, arson, and life in a vanishing land - Hesse, Monica (Dreamscape Audio, 2017)
Documents the trial of a man charged with dozens of counts of arson in a rural Virginia county, sharing insight into his struggles with addiction, his relationship with his accomplice girlfriend, and the impact of the fires on their community.